Cruel Modernity - Franco, Jean, 1924- (Book collections on Project MUSE., 2013)
"Cruel Modernity is a tour de force by Jean Franco, the major figure in Latin American cultural criticism. Franco has an unfailing sense of the political and in Cruel Modernity she reveals a kind of madness in the nation-building business. The widespread perpetration of cruelty and gratuitous violence that she seeks to understand-killing, raping, maiming-are primary and archaic impusles of permissive masculinities gone berserk, precisely because of their failures in constructing the nation state."--Ileana Rodríguez, author of Liberalism at Its Limits: Crime and Terror in the Latin American Cultural Text.